Shakespeare and the uses of antiquity : an introductory essay - Martindale, Charles; Martindale, Michelle, 1951- (London ; New York : Routledge, 1994)
In Shakespeare and the Uses of Antiquity, Charles and Michelle Martindale take issue with the recent academic tendency to exaggerate Shakespeare's expertise in the classics. Instead they show how the playwright used his restricted knowledge of the classics to create a remarkably convincing picture of the classical world. Although almost a third of his plays are set in the ancient world and are rich in allusions to classical mythology, history and ideas, Shakespeare received only grammar school training in this discipline--a far cry from the scholarly knowledge he would otherwise seem to posses.
Includes bibliographical references (pages 216-218) and indexes.
Print version record.
eBooks on EBSCOhost
Keywords: Shakespeare, William, -- 1564-1616 -- Knowledge -- Literature; Shakespeare, William, -- 1564-1616 -- Knowledge -- Rome; Shakespeare, William, -- 1564-1616; Shakespeare, William, -- (1564-1616) -- Connaissances -- Littérature classique; Historical drama, English -- History and criticism; Classicism -- England -- History -- 16th century; Civilization, Classical, in literature; Mythology, Classical, in literature; Rome -- In literature; Théâtre historique anglais -- Histoire et critique; Classicisme -- Angleterre -- Histoire -- 16e siècle.; Mythologie ancienne dans la littérature.; LITERARY CRITICISM -- Shakespeare; DRAMA -- Shakespeare; Civilization, Classical, in literature; Classicism; Historical drama, English; Literature; Mythology, Classical, in literature; England; Rome (Empire); Histoire ancienne dans la littérature.; 1500-1599; Drama in English -- Shakespeare, William, 1564-1616. -- Influence of classical literatures; Criticism, interpretation, etc; History; Literature